Controlling and quantifying oxygen functionalities on hydrothermally and thermally treated single-wall carbon nanotubes - Romanos, G.E.; V. Likodimos; Marques, R.R.N.; Steriotis, T.A.; Papageorgiou, S.K.; Faria, J.L.; Figueiredo, J.L.; Silva, A.M.T.; P. Falaras (Journal of Physical Chemistry C, 2011)
The effects of hydrothermal and thermal treatments on surface oxygen functionalization of single-wall carbon nanotubes (SWNTs) were quantitatively investigated by means of water adsorption/desorption, temperature-programmed desorption (TPD), Raman spectroscopy, thermogravimetric analysis, and nitrogen porosimetry. SWNTs hydrothermally treated under mild acidic conditions were compared to highly purified reference materials heavily functionalized under aggressive reflux conditions. Water adsorption/desorption and TPD analysis were successfully combined to determine the nature, concentration, thermal stability, and acidic strength of the oxygen functional groups on the SWNT's surface. These results were correlated to Raman spectroscopy data that allowed identifying the marked evolution of the defect-activated phonon modes of SWNTs. The concomitant charge transfer effects were differentiated through the distinct variation of both first- and second-order Raman modes as a function of the amount and acidity of the surface oxygen groups as well as the SWNT's chirality. In addition, analytical investigations on thermally treated SWNTs in mild oxidative (in air) and pyrolytic conditions (under Ar) confirmed the formation of amorphous carbon that depends primarily on the acidification process, although a significant fraction of functional groups remains attached on the SWNTs' walls rather than on carboxylated carbonaceous fragments. Quenched solid density functional theory (QSDFT) analysis of the bimodal pore size distribution of the functionalized SWNTs revealed pronounced variations of the underlying microporous and mesoporous structure, associated with the diverse effects of the packing between SWNT bundles and the closer aggregation of individual carbon nanotubes upon surface oxidation and thermal treatment. The SWNTs functionalization procedure can be effectively controlled and quantified, and the optimum conditions can be defined in relation to the desired physicochemical properties and pore structure characteristics for specific applications. © 2011 American Chemical Society.